Assessing susceptibility for polycyclic aromatic hydrocarbon toxicity in an in vitro 3D respiratory model for asthma - Valdez, Reese M.; Rivera, Brianna N.; Chang, Yvonne; Pennington, Jamie M.; Fischer, Kay A.; Löhr, Christiane V.; Tilton, Susan C. (Frontiers in Toxicology, 2024)
There is increased emphasis on understanding cumulative risk from the combined effects of chemical and non-chemical stressors as it relates to public health. Recent animal studies have identified pulmonary inflammation as a possible modifier and risk factor for chemical toxicity in the lung after exposure to inhaled pollutants; however, little is known about specific interactions and potential mechanisms of action. In this study, primary human bronchial epithelial cells (HBEC) cultured in 3D at the air-liquid interface (ALI) are utilized as a physiologically relevant model to evaluate the effects of inflammation on toxicity of polycyclic aromatic hydrocarbons (PAHs), a class of contaminants generated from incomplete combustion of fossil fuels. Normal HBEC were differentiated in the presence of IL-13 for 14 days to induce a profibrotic phenotype similar to asthma. Fully differentiated normal and IL-13 phenotype HBEC were treated with benzo[a]pyrene (BAP; 1 -40 µg/mL) or 1% DMSO/PBS vehicle at the ALI for 48 hrs. Cells were evaluated for cytotoxicity, barrier integrity, and transcriptional biomarkers of chemical metabolism and inflammation by quantitative PCR. Cells with the IL-13 phenotype treated with BAP result in significantly (p<0.05) decreased barrier integrity, less than 50% compared to normal cells. The effect of BAP in the IL-13 phenotype was more apparent when evaluating transcriptional biomarkers of barrier integrity in addition to markers of mucus production, goblet cell hyperplasia, type 2 asthmatic inflammation and chemical metabolism, which all resulted in dose-dependent changes (p<0.05) in the presence of BAP. Additionally, RNA sequencing data showed that the HBEC with the IL-13 phenotype may have increased potential for uncontrolled proliferation and decreased capacity for immune response after BAP exposure compared to normal phenotype HBEC. These data are the first to evaluate the role of combined environmental factors associated with inflammation from pre-existing disease and PAH exposure on pulmonary toxicity in a physiologically relevant human in vitro model.